Departure time choice behavior in commute problem with stochastic bottleneck capacity: experiments and modeling - Liu, Qiumin; Lu, Dongxu; Jiang, Rui; Han, Xiao; Liu, Ronghui; Gao, Ziyou (Transportmetrica (Abingdon, Oxfordshire, UK), 2023)
The effect of environmental uncertainty on equilibrium patterns is of vital importance to understand travel choice behavior. This paper conducted a laboratory experiment to investigate the effects of stochastic bottleneck capacity on departure time choice behavior. In the experiment, the bottleneck capacity varied stochastically from round to round, and two different scenarios with different information feedback were investigated. Our experimental results showed that the relationship between the mean travel cost and the standard deviation of travel cost on each departure time was fitted approximately linearly with a positive slope , indicating subjects were more likely to minimize their travel cost budget rather than their mean travel cost. Also, we found that the feedback on costs of all departure times resulted in a smaller than the feedback on the subjects' own travel cost only. We propose a reinforcement learning model to reproduce the main experimental findings.